Avaliação termoanalítica da degradação do polipropileno sobre os materiais compósito de perlita expandida impregnada com óxido de cério, zeólita H-Y e a mistura compósito/zeólita - Barbosa, Rodrigo Victor (2021)
The objective of this work was to evaluate the thermal degradation of polypropylene on the composite of expanded perlite impregnated with cerium oxide, hereinafter referred to as Ce-PER, as well as to compare it with the degradation of PP when using a commercial HY zeolite and a mixture of CePER with HY. Cerium oxide was added to the expanded perlite by means of the excess solvent co-impregnation method. The materials were analyzed by the techniques of XRD, XRF, SEM, TG/DTG and acidity test by thermal desorption of n-butylamine. The degradation profile of polypropylene was evaluated in a thermobalance. The degradation of PP was catalyzed when mixtures containing 30%H-Y + PP and 15%H-Y + 15%Ce-PER + PP were used. On the other hand, PP received a thermal stabilization effect when using the mixtures containing 10% and 30%Ce-PER + PP. The acidity analysis yielded the total acid site density values for zeolite H-Y (2,30 mmol) and for Ce-PER (0,2 mmol).